Outcome of angioembolization for blunt renal trauma in haemodynamically unstable patients: 10‐year analysis of Queensland public hospitals. Issue 9 (12th August 2020) - Desai, Devang; Ong, Michelle; Lah, Kevin; Clouston, John; Pearch, Ben; Gianduzzo, Troy
Abstract: Background: The aim of the study was to evaluate whether angioembolization is an appropriate alternative method for the management of blunt renal trauma in haemodynamically unstable patients. Methods: A retrospective analysis was conducted from 2002 to 2012 at three tertiary trauma hospitals in the state of Queensland. Patients who had blunt renal trauma and underwent renal angioembolization or had a trauma nephrectomy were identified using patient records and operating theatre and interventional radiology databases. The inclusion criteria were – haemodynamically unstable patients with blunt renal trauma treated with angioembolization, above the age of 16 years. Patients who underwent angioembolization for other causes such as: penetrating renal trauma, post‐procedure, renal tumours, renal angiomyolipomas or arteriovenous malformations were excluded. Patients below the age of 16 were also excluded. Post‐embolization renal function, blood pressure, morbidity and mortality were analysed using the paired t 2 test. Results: A total of 668 renal trauma patients were identified during this period. Sixteen patients underwent angioembolization for blunt renal trauma. Post‐procedure renal function normalized without any hypertension with the median follow up being 4 months. Four patients had post‐embolization complications including a urinoma, two devascularized kidneys and one ureteric stricture requiring nephrectomy. There was no mortality. Conclusion: Selective angioembolization, where feasible, is an alternative method in the management of haemodynamically stable patients with blunt renal trauma maximizing nephron sparing and producing acceptable long‐term outcomes with avoidance of the morbidity of trauma nephrectomy. This is the first study that we know of in Australia analysing the outcome of angioembolization for blunt renal trauma. Abstract : This article demonstrates our experience in Queensland of the use of angioembolization in the management of blunt renal trauma in transiently haemodynamically unstable patients.